Eradicating Land Mafia Through Comprehensive and Innovative Approaches in the Reform of Indonesian Agrarian Law - Nelly Azwani Sinaga; Ikhsan Lubis; Duma Indah Sari Lubis; Andi Hakim Lubis (Jurnal Hukum Magnum Opus, 2026)
Land mafia practices in Indonesia continue to pose serious threats to legal certainty, economic development, and social justice. This study aims to examine the effectiveness of Indonesia’s agrarian legal framework in combating land mafia and to propose comprehensive and innovative strategies to strengthen land governance. Using a normative juridical method with a statutory and conceptual approach, this research analyzes legal provisions, institutional frameworks, and supporting technologies relevant to land registration and regulation. The findings reveal that the current negative publication system under the Basic Agrarian Law (UUPA) creates legal loopholes that are exploited by land mafia networks. The study proposes a shift toward a positive publication system, integration of secure digital platforms (such as blockchain-based land registries), institutional reform, and enhanced public participation in land oversight. The novelty of this research lies in its interdisciplinary strategy that combines legal reform, technology, and civic engagement to build an accountable, transparent, and corruption-resistant land governance system in Indonesia.